Effect of Oxygen-containing Functional Groups on the NO2 Adsorption and Reduction by Activated Carbon A Density Functional Theory Calculation Study - Hao, Tong (Langmuir : the ACS journal of surfaces and colloids, 2025)
The activated carbon effectively removes nitrogen dioxide (NO2) gas from environmental air, and its adsorption-reduction performance is significantly influenced by surface oxygen-containing functional groups (OFGs). However, the internal mechanisms of different OFGs in the complete reaction processes remain unclear. Based on previous studies and experimental characterization results, this paper selects two typical carbon edge structure models and six different OFGs as fundamental models. Using density functional theory, wave function analysis, and thermodynamic and kinetic analyses, we comprehensively investigate the microscopic reaction pathways of the NO2 molecule on carbon edge structures modified with OFGs. The results show that most OFGs inhibit NO2 adsorption and N-O bond cleavage via van der Waals interactions, while their impact on NO desorption is negligible due to localized effects. Thermodynamic and kinetic analyses jointly validated these findings. Importantly, the results highlight that zigzag edge structures exhibit superior reactivity toward NO2 reduction, suggesting that carbon materials prepared below 400 °C with minimal OFG incorporation are more favorable. This dual-optimization strategy provides practical guidance for enhancing the NO2 conversion performance, offering a molecular-level foundation for the rational design of advanced carbon-based adsorbents or catalysts